LEARNING TRAJECTORY OF QUADRATIC INEQUALITY - Tamba, Kimura Patar; Saragih, Melda Jaya; Listiani, Tanti (Universitas Pelita Harapan, 2018)
A learning trajectory offers a description of key aspects in planning mathematics learning. It also helps teachers follow and interpret students’ mathematical thinking, so that learning can be developed in accordance with the characteristics of students, and even become a tool for teachers to develop curriculum. There are three main components of learning trajectory: learning goals, learning activities, and hypothetical learning processes. In this article, we constructed a learning trajectory of the quadratic inequality. This qualitative study used didactical design research with 105 grade 10 students as the participants. In the prospective analysis step, didactic design, learning obstacle, and quadratic inequality system were analyzed. Based on the results of this analysis, we constructed hypothetical learning trajectories in the form of didactical design. Then, hyphothetical learning trajectories were implemented in the learning process. Student’s responses were analyzed qualitatively. Results of this analysis were used to revise the learning trajectory in order to obtain alternative trajectory learning outcomes of theoretical and empirical analysis. Finally, this article offers an alternative learning trajectory of quadratic inequalities that are different from the existing learning trajectories presented in the current textbook. The learning trajectory that is offered is the learning quadratic inequality which starts from the function approach. BAHASA INDONESIA ABSTRACT: Learning trajectory (LT) menawarkan sebuah deskripsi akan aspek kunci dalam perencanaan pembelajaran matematika. LT juga membantu guru belajar dalam mengikuti dan menginterpretasi cara berpikir matematisnya siswa, sehingga pembelajaran dapat dikembangkan sesuai dengan karateristik siswa, bahkan menjadi alat bagi guru untuk mengembangkan kurikulum. Ada tiga komponen utama dari learning trajectory, yaitu: tujuan pembelajaran (learning goals), kegiatan pembelajaran (learning activities) dan hipotesis proses belajar siswa (hypothetical learning process). Dalam artikel ini akan dikonstruksi sebuah LT pertidaksamaan kuadrat. Penelitian ini menggunakan pendekatan kualitatif dengan didactical design research. Adapun partisipan sebanyak 105 siswa kelas X. Pada awal penelitian ini, dilakukan analisis propektif yaitu analisis atas materi pertidaksamaan kuadrat, hambatan belajar dan tingkat berpikir siswa. Kemudian dari hasil analisis ini disusunlah Hipotetical Learning Trajectories yang berupa desain didaktis. Desain didaktis berdasarkan Hypotetical Learning Trajectories ini diimplementasikan dalam pembelajaran. Respon siswa dianalisis secara kualitatif. Hasil analisis ini digunakan untuk merevisi Learning Trajectory, sehingga diperoleh Learning Trajectory alternatif hasil analisis teoritik dan empirik. Akhirnya, artikel ini menawarkan sebuah alternatif learning trajectory pertidaksamaan kuadrat yang berbeda dengan learning trajectories yang ada pada buku pelajaran sekarang. Learning trajectory yang ditawarkan adalah pembelajaran pertidaksamaan yang dimulai dengan pendekatan fungsi.